Attentional strategy moderates effects of pain catastrophizing on symptom-specific physiological responses in chronic low back pain patients. - Quartana PJ; Burns JW; Lofland KR (Journal of Behavioral Medicine, 2007)
In the present study, we examined whether experimentally-manipulated attentional strategies moderated relations between pain catastrophizing and symptom-specific physiological responses to a cold-pressor task among sixty-eight chronic low back patients. Patients completed measures of pain catastrophizing and depression, and were randomly assigned to sensory focus, distraction or suppression conditions during a cold pressor. Lumbar paraspinal and trapezius EMG, and cardiovascular responses to the cold pressor were assessed. Attentional strategies moderated the relation between pain catastrophizing and lumbar paraspinal muscle, but not trapezius muscle or cardiovascular responses. Only for participants in the suppression condition was catastrophizing related significantly to lumbar paraspinal muscle responses. Depressed affect did not account for this relation. These findings indicate that 'symptom-specific' responses among pain catastrophizers with chronic low back depend on how they attend to pain-related information. Specifically, it appears that efforts to suppress awareness of pain exaggerate muscular responses near the site of injury.